2010
DOI: 10.1177/1947601910392984
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles for SSeCKS/Gravin/AKAP12 in the Control of Cell Proliferation, Cancer Malignancy, and Barriergenesis

Abstract: Emerging data suggest that SSeCKS/Gravin/AKAP12 (“AKAP12”), originally identified as an autoantigen in cases of myasthenia gravis, controls multiple biological processes through its ability to scaffold key signaling proteins such as protein kinase (PK) C and A, calmodulin, cyclins, phosphoinositides, the so-called “long” β-1,4 galactosyltransferase (GalTase) isoform, Src, as well as the actin cytoskeleton in a spatiotemporal manner. Specialized functions attributed to AKAP12 include the suppression of cancer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
94
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 104 publications
5
94
1
Order By: Relevance
“…To identify which AKAP may be responsible for the effects of st-HT31, we studied the effect of CSE and st-Ht31 on the expression of AKAP9 and AKAP12, which maintain endothelial barrier function and the blood-retinal barrier, respectively (8,35). In addition, AKAP12 regulates E-cadherin expression in prostate epithelial cells (1), and AKAP5 interacts with cadherins (10).…”
Section: Disruption Of Akap Complexes Prevents Cse-induced Loss Of Akmentioning
confidence: 99%
“…To identify which AKAP may be responsible for the effects of st-HT31, we studied the effect of CSE and st-Ht31 on the expression of AKAP9 and AKAP12, which maintain endothelial barrier function and the blood-retinal barrier, respectively (8,35). In addition, AKAP12 regulates E-cadherin expression in prostate epithelial cells (1), and AKAP5 interacts with cadherins (10).…”
Section: Disruption Of Akap Complexes Prevents Cse-induced Loss Of Akmentioning
confidence: 99%
“…Further confounding the issue, PKC␣ promotes proliferation of androgen receptor-negative PC-3 CaP cells, whereas it along with PKC␦ promotes apoptosis (17) in the androgen-responsive cell line LNCaP (18 -22). Our laboratory identified SSeCKS (for Src-suppressed C kinase substrate) as a substrate of PKC whose expression is severely downregulated in src-and ras-transformed cells (23,24). Subsequently, Jaken and co-workers (25,26) identified STICK72, which encodes a "Ͼ200-kDa" PKC substrate with PS binding activity, as identical to SSeCKS.…”
mentioning
confidence: 99%
“…SSeCKS has many similarities to the well studied PKC substrate MARCKS, although they have quite different sequences and molecular weights. These include transcriptional suppression by v-src, PS-induced binding to PKC, N-terminal myristoylation, a predicted rodlike shape, heat stability, severely retarded mobility on SDS-PAGE, Ca 2ϩ -dependent calmodulin binding, and PMA-induced translocation to perinuclear sites (24,27). We recently showed that SSeCKS can associate with PKC␣, -␦, and -⑀ isozymes when overexpressed (28).…”
mentioning
confidence: 99%
“…Aberrant DNA methylation in the promoter region has been shown to specifically silence AKAP12 in Src-and Ras-transformed fibroblasts. 10 Reexpression of AKAP12 in vitro and in vivo suppresses oncogenic growth, 21 while overexpression of AKAP12 leads to cell cycle arrest. 22 In line with this, cells react with increased AKAP12 expression levels upon mitogenic stimuli.…”
Section: Resultsmentioning
confidence: 99%